The Fuction of Nuwo Panggung in Flood Disaster Mitigation Kelumbaya District, Tanggamus - Amalia Anisafira Budi; Puji Hardati; Rahma Hayati (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The culture of the Lampung Tribe dominates the culture in Kelumbayan District. As with other tribes in Indonesia, the Lampung tribe makes culture an identity that is attached to every member of the tribe. Local wisdom is part of the culture.Â Qualitative researchÂ is a process of understanding human or social phenomena by creating a comprehensive and complex picture that can be presented in words, reporting detailed views obtained from informant sources, and being carried out in natural settings. Instruments in the research were the observation of data collection, interviews, and documents. The local wisdom of nuwo onstage as a traditional house for the Lampung tribe in Kelumbayan District is still commonly found in Kelumbayan District, especially in Pekon Umbar, Napal, and Susuk. Various traditional Lampung houses are based on their shape, including the Slow Dalom Building, the Slow Pesagi, the Slow Kejayaan, the Slow Sakura, and the Slow Dalom. Nuwo Panggung in Kelumbayan District is included in the Lamban Pesagi, which has three building parts, namely the upper, middle, and lower sections. The Nuwo stage with the Lalan Pesagi type was built using a basic pattern of cylinders, cubes, and pyramids.